(untitled) (Bangladesh Journal of Plant Taxonomy, 2016)
One hundred seventy seven species belonging to 88 genera under 14 natural orders are determined to have been recorded in the third volume of J.D. Hookers, the Flora of British India from the area now fall in Bangladesh. These taxa are enumerated with updated nomenclature and current taxonomic status following ICN and Cronquists system of plant classification respectively resulting in 169 species under 93 genera and 14 families. Collection locality with collectors name of each species wherever available, as cited in protologue, is also included. Bangladesh J. Plant Taxon. 23(2): 143-160, 2016 (December)